Tea Constituent in Protecting Glyphosate Effect on Human Breast Cancers Cells (MCF-7) Growth - Batubara, Irmanida; Suprihatini, Rohayati; Mariya, Silmi; Achmadi, Suminar Setiati; Sokoastri, Valentina; Mulyatni, Agustin Sri; Hakim, Arif Rakhman (Syarif Hidayatullah State Islamic University, 2023)
Glyphosate, which has been documented as a contaminant in tea, promotes the proliferation of human breast cancer cells (MCF-7). Tea, on the other hand, includes various antioxidants, including epigallocatechin gallate (EGCG), which may protect against cancer cell proliferation. The purpose of this research is to determine the preventive effect of concentrated brewed green tea on MCF-7 development caused by glyphosate. The glyphosate concentration that promotes MCF-7 development was determined using a serial concentration of glyphosate. Glyphosate concentrations of up to 64 mg/L were shown to have no effect on MCF-7 cell proliferation. Concentrated brewed tea and EGCG 200 mg/L have the potential to suppress MCF-7 cell proliferation in the presence of glyphosate up to 512 mg/L. The combination of glyphosate and concentrated brewed tea or EGCG protects against glyphosate toxicity via altering the expression of tumor suppressor protein (p53).